2016
DOI: 10.1155/2016/1602761
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Under-Five Mortality in High Mortality Regions of Ethiopia: An Analysis of the 2011 Ethiopia Demographic and Health Survey Data

Abstract: The study was a secondary analysis of existing data from the 2011 Ethiopia Demographic and Health Survey data. Of the 2097 live births recorded in Affar, Somali, Benishangul-Gumuz, and Gambela regions of Ethiopia between 2006 and 2011, 366 deaths before the age of five years were reported. The univariable and multivariable Cox proportional regression models were fitted to select the factors affecting under-five mortality in these regions. The model revealed that under-five mortality significantly associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

50
71
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(128 citation statements)
references
References 16 publications
50
71
4
3
Order By: Relevance
“…Thus, the likelihood of under-ve mortality was 1.5 times high among children residing in rural areas as compared with their urban counterpart. This concurs with previous studies in and outside Ethiopia (4,10,16,18).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the likelihood of under-ve mortality was 1.5 times high among children residing in rural areas as compared with their urban counterpart. This concurs with previous studies in and outside Ethiopia (4,10,16,18).…”
Section: Discussionsupporting
confidence: 93%
“…In our study using the Strati ed Cox PH model, the multiple or twin birth type children had more than 5 times higher risk of death compared with single birth type children. Many studies showed that birth type of child was a signi cant determinant factor (8)(9)(10). But, other study from Nigeria had reported the reverse of this result.…”
Section: Discussionmentioning
confidence: 98%
“…The current study showed that illiteracy of mothers and associated edema at admission were found to be associated with post-discharge mortality in children with SAM admitted to the hospital. Mothers' education is one of the main determinants of under-five mortality [16]. In the current study, we found that maternal illiteracy was associated with 7-fold increased risk of post-discharge mortality.…”
Section: Discussionsupporting
confidence: 52%
“…This finding was consistent with other studies. [10,[13][14][15] An unexpected finding was that the risk of U5CM decreased as family size of the household increased, meaning that children in a larger household had a better chance of surviving to see their fifth birthday. [9,12,[16][17][18] This is due to the fact that a mother who has had more than one child would have the experience to seek healthcare services to keep the child healthy.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in agreement with other studies. [14,19,20] U5CM is reduced if mothers deliver their children at a healthcare centre, where they receive appropriate assistance from skilled professionals during birth, as well as information on how to care for the child and the benefits of the healthcare system. [21]…”
Section: Discussionmentioning
confidence: 99%